Microvascular Reconstruction of Segmental Mandibular Defects without Tracheostomy. (10th November 2014) - Moubayed, Sami P.; Barker, Daniel A.; Razfar, Ali; Nabili, Vishad; Blackwell, Keith E.
Abstract : Objective: To report our experience with mandibular resection and reconstruction using vascularized bone‐containing free flaps without an elective tracheostomy. Study Design: Case series with chart review. Setting: Tertiary referral hospital center. Subjects and Methods: Sixty‐six patients undergoing mandibular reconstruction with vascularized bone‐containing free flaps without an elective tracheostomy were identified between 1995 and 2013. We describe patient, tumor, and surgical factors and report perioperative outcomes in this population. Results: Most patients underwent fibula free flap reconstruction (n = 61, 92.44%). The 4 most frequent indications for resection were osteoradionecrosis, parotid carcinoma, oral squamous cell carcinoma, and osteomyelitis. Bone defects ranging from 4.0 to 13.0 cm were reconstructed, and associated soft‐tissue defects were reconstructed with skin paddle sizes ranging from 24.0 to 450.0 cm 2 . There was only 1 patient with a bilateral central mandibular defect, and there were no tongue/pharyngeal soft‐tissue defects or bilateral neck dissections. One case required emergent tracheostomy on postoperative day 1, and 2 more patients developed respiratory complications. There were no cases of perioperative death or flap failure. Conclusion: Mandibular free flap reconstruction is feasible without an elective tracheostomy in a subset of carefully selected patients without bilateral central mandibular defects, tongue/pharynx defects, or bilateral neck dissection.